Peran Self-Esteem dan Dukungan Sosial terhadap Career Decision Making-Self Efficacy pada Mahasiswa - Wijaya, Feilicya Aurellia; Virlia, Stefani (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
Besides completing final assignments, final-year students also have to start thinking about their careers after graduation. There are still many final-year students who are unsure about planning their future careers due to a lack of soft skills and hard skills, past failures, minimal experience, unclear job information, and lack of support from parents and the environment. If this continues, it can affect their self-confidence in deciding on the career they previously wanted. This research reviews the role of self-esteem and social support on career decision-making self-efficacy. This research was conducted using quantitative methods and a correlational design, involving 149 final-year students (21-25 years) as research participants. Data was collected using the accidental sampling technique through an online questionnaire survey. The variables self-esteem and social support influence CDMSE with a p-value below 0.05 and a contribution of 45.8%, thus indicating that the hypothesis is accepted.